Lifestyle Differences Between Rural and Urban Communities In Hypertension Prevention - Arief Shofyan Baidhowy; Wahyu Haniq Maftuhah; Yunie Armiyati; Edy Soesanto (Media Keperawatan Indonesia, 2024)
Indonesian society is undergoing an epidemiological transformation as the burden of disease shifts from infectious diseases to non-communicable diseases. Hypertension has become a global problem and is one of the non-communicable diseases that requires special attention. The management of risk factors for hypertension is lifestyle. Rural and urban play an important role in lifestyle changes so that people in both places are at risk of hypertension. So it is necessary to see the differences in the lifestyles of urban and rural communities to prevent hypertension. The purpose of this study was to determine the differences in lifestyle that occur in urban and rural communities in preventing hypertension. This research is a type of descriptive analytic with a cross-sectional design. The sample in this study were 150 respondents selected by stratified random sampling technique. The results of this study show there is a significant relationship between lifestyle in rural and urban communities. Rural and urban lifestyles affect the prevention of patients with hypertension.